Electron energy probability function and dust charge in the temporal afterglow of a plasma with large dust density - Denysenko, I.B.; Ivko, S.; Azarenkov, N.A.; Burmaka, G. (Вопросы атомной науки и техники, 2018)
Analytical expressions for the electron energy probability function (EEPF) in an argon plasma afterglow with large dust density, which are obtained from the homogeneous Boltzmann equation for different steady-state EEPFs (including both Maxwellian and Druyvesteyn distributions at electron energies larger than the dust-surface potential), are presented. The casewhen the rate for electron-neutral momentum-transfer collisions is independent of the electron energy is considered. It is analyzed how the EEPF shape depends on the afterglow time and the decay time of dust charge. It is also found how the decay time of dust charge depends on the decay time of effective electron temperature and that of electron density. The conditions when the energy derivative of the EEPF may be positive are obtained.